2020
DOI: 10.1002/ccd.29322
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐term follow‐up of balloon pulmonary angioplasty for inoperable chronic thromboembolic pulmonary hypertension: An experience in Latin America

Abstract: Objectives To describe the characteristics of patients who undergo balloon pulmonary angioplasty (BPA) for inoperable chronic thromboembolic pulmonary hypertension (CTEPH) and report the mid‐term outcomes. Background BPA has been recently introduced in Latin America. Mid‐term results have not been published. Methods Prospective Chilean Registry of inoperable CTEPH patients who underwent BPA. Clinical variables were analyzed at baseline, after each procedure and at follow‐up. Hemodynamic variables were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…The number of periprocedural complications in the study group does not differ from those found in European and American reports [10,13,14,[18][19][20][21][22], with the procedure methodology and many years of experience documented in Japanese publications significantly contributing to reducing the number of deaths [5,16,17,23]. The available publications present various approaches to using additional endovascular techniques for BPA, but in the studied single-center group, this translated into treatment effectiveness and safety [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The number of periprocedural complications in the study group does not differ from those found in European and American reports [10,13,14,[18][19][20][21][22], with the procedure methodology and many years of experience documented in Japanese publications significantly contributing to reducing the number of deaths [5,16,17,23]. The available publications present various approaches to using additional endovascular techniques for BPA, but in the studied single-center group, this translated into treatment effectiveness and safety [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 70%
“…The essence of this procedure is the percutaneous insertion of a balloon catheter into the pulmonary artery and inflation of the fibrotic remnant of the thrombus, which improves perfusion, reduces vascular resistance and pressure in the vessel, and improves the prognosis. After the first reports from 1988 and initial unsatisfactory results, the method has been improved in recent decades and has consolidated its position in treating CTEPH patients [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…With the progress of technology and the accumulation of clinical experience, BPA can effectively improve hemodynamics, cardiac function, and symptoms without severe complications [4][5][6][7][8][9]. Nowadays, it has been an effective alternative therapy for patients who cannot undergo PEA or with residual or recurrent pulmonary hypertension after PEA [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Such patients may be subjected to a series of balloon pulmonary angioplasty (BPA) procedures [ 6 , 7 , 8 , 9 , 10 ]. An assessment of the effects of subsequent BPA sessions, as well as long-term follow-up of patients after the completed therapy, requires, for example, invasive examination, such as right heart catheterization (RHC) [ 11 ]. The main purpose of this study is to create a simple electrocardiographic (ECG) scale, useful in clinical practice, which could be used to monitor the efficacy of interventional therapies, such as BPA, in patients with CTEPH.…”
Section: Introductionmentioning
confidence: 99%